Experiences of having an adult sibling with a mental illness: an interpretative phenomenological analysis - Flannigan, Raylene (Rhodes University, Faculty of Humanities, Department of Psychology, 2017)
Mental illness has a significant impact on the life of an individual, however not only on the individual but on the family as well. A considerable amount of research has been carried out regarding the experiences of family members internationally. However, in South Africa (SA) there is inadequate information regarding the experiences of families, especially adult siblings, of individuals with a mental illness. Specifically, there is a lack of research investigating individuals' perceptions of their brother or sister's mental illness as well as how this affects the sibling relationship. It is for this reason that the current study aimed at exploring the lived experiences of 'black1' isiXhosa speaking individuals who have a sibling with a mental illness. The study employed Interpretative Phenomenological Analysis (IPA) as its qualitative approach. A sample of five participants between the ages of 20-50 years was selected through purposive and snowballing sampling techniques. Semi-structured interviews were utilised and were transcribed and analysed based on the IPA framework. The analysis of the participants' transcripts provided three master themes, which are supported by subordinate themes. The master themes are: 1) experiencing the sibling as a burden post diagnosis, 2) positive experiences from the sibling's mental illness, 3) participant's experiences of their sibling's treatment and the mental health care system. Participants experienced financial burden as well as the burden of caregiving as a result of their sibling's mental illness; these are understood as being subjective and objective burdens. While no change was experienced within the sibling relationship, the siblings' mental illness was experienced as affecting the sibling relationship due to the socioeconomic status of the participants and stigma. The findings support and expand on the growing knowledge of adult sibling relationships and mental illness.
Keywords: Mentally ill -- Family relationships; Mentally ill -- Care -- South Africa; Mental illness -- Public opinion -- South Africa; Mentally ill -- Deinstitutionalization; Brothers and sisters of people with disabilities; Brothers and sisters of people with disabilities -- Psycnology; Brothers and sisters of people with disabilities -- Case studies -- South Africa -- Makhanda